PHYSICOCHEMICAL PROPERTIES AND COz ABSORPTION CHARACTERISTICS OF AQUEOUS AMINO ACID SALTS AND PIPERAZINE BLENDS - SHAIKH, MUHAMMAD SHUAIB (2017)
Amino acid salt solutions have emerged as an efficient alternative to alkanolamines for C02 capture. In this work, the amino acid salts, aqueous sodium glycinate (SG), aqueous sodium 1-prolinate (SP) and their piperazine (PZ) blends (SG + PZ and SP + PZ) were prepared and investigated